UTILIZATION KOLONG TIN MINING TO IMPROVE KNOWLEDGE AND ATTITUDE STUDENTS FOR ENVIRONMENT (Quasi Experiment Students In Class XI SMAN 1 Sungaiselan Central Bangka Bangka Belitung Islands) - Susanti, Hartini (Indonesia University of Education, 2015)
Tin mining pit is formed due to mining activities in Kecamatan Sungaiselan. One of the ways to prevent the spread of damage caused by the tin mining activities is to foster the knowledge and attitude towards the environment to the society. Through knowledge and attitude, it is expected that the society would aware in maintaining the quality of the environment thus it can minimize the impact of the damage. Knowledge and attitude towards the environment can be tought in a formal institution to the students thus they are expected to spread their knowledge and attitude to their parents and to the society. The way to cultivate knowledge and attitude of the students is to make the tin mining as a source of learning by analyzing the effect of learning resources on knowledge and attitude, also the advantages and disadvantages of learning through field studies and the medium of film /video by using quantitative approach through experimental method. The sample of this research is 54 second semester students from XI IS SMAN 1 Sungaiselan, year 2014/2015. The data were collected by using test, worksheets, and questionnaires. The data were analyzed by using statistical normality test, homogeneity and T test with SPSS version 21. The statistical results showed: 1) there are differences in knowledge and attitude by using the medium of film /video before and after treatment, 2) there are differences in knowledge and attitudes by usingg field studies method before and after treatment, 3) recommend using the environment as the source of learning.Keywords: Kolong Tin Mining, Learning Resources, Knowledge, Attitude.